Da “revolução funcionalista” às novas sínteses antropológicas - Barretto, Maria Amália Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 1983)
O trabalho procura analisar as novas linhas antropológicas surgidas a partir das perspectivas teóricas funcionalistas.

This paper tries to analyse the new anthropological currents that have appeared from the theoretical funcionatistic perspectives.
From the “funcionalist revolution” up to new anthropological synthesis
Keywords: Funcionalismo; Malinowski e Radcliffe Brown; Evolucionismo; Difusionismo; Estruturalismo: Lévi-Strauss e Victor Turner; Funfionalism: Malinowski and Radcliffe-Brown; Evolutionism; Difusionism; Structuralism: Lévi-Strauss and Victor Turner